2015
DOI: 10.1021/acs.accounts.5b00303
|View full text |Cite
|
Sign up to set email alerts
|

Seduction of Finding Universality in Sputtering Yields Due to Cluster Bombardment of Solids

Abstract: Universal descriptions are appealing because they simplify the description of different (but similar) physical systems, allow the determination of general properties, and have practical applications. Recently, the concept of universality has been applied to the dependence of the sputtering (ejection) yield due to energetic cluster bombardment versus the energy of the incident cluster. It was observed that the spread in data points can be reduced if the yield Y and initial projectile cluster kinetic energy E ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Nowadays, gas cluster ion beams (GCIB) are applicable to molecular depth profiling of a large variety of organic and polymer materials but, under the experimental conditions suitable for such purpose (typically quite large cluster ions, with thousands atoms per cluster), they appear rather inefficient in sputtering inorganic materials . For example, considering a typical case of an Ar n cluster with 10 eV/atom (such as 20 keV Ar 2000 ) the sputtering yield of inorganics (Si, Au, SiO 2 ) is reported to be about 2 orders of magnitude lower than that for organic targets (PMMA, PS, Irganox 1010) . Actually, the maximum sputtering yield of inorganics with Ar n (energy of some 10 keV) is reported in a size range of 10 < n < 200 (i.e.…”
mentioning
confidence: 99%
“…Nowadays, gas cluster ion beams (GCIB) are applicable to molecular depth profiling of a large variety of organic and polymer materials but, under the experimental conditions suitable for such purpose (typically quite large cluster ions, with thousands atoms per cluster), they appear rather inefficient in sputtering inorganic materials . For example, considering a typical case of an Ar n cluster with 10 eV/atom (such as 20 keV Ar 2000 ) the sputtering yield of inorganics (Si, Au, SiO 2 ) is reported to be about 2 orders of magnitude lower than that for organic targets (PMMA, PS, Irganox 1010) . Actually, the maximum sputtering yield of inorganics with Ar n (energy of some 10 keV) is reported in a size range of 10 < n < 200 (i.e.…”
mentioning
confidence: 99%
“…The second change was needed in order to take into account the fact that the binding energies U 0 , for atomic and molecular solids, can differ several times; thus, their effect on the sputtering efficiency cannot be neglected. 14,17 The results of MD simulations showed that there are obvious similarities in the sputtering mechanisms between the atomic and molecular solids for almost 3 orders of magnitude variation of (E/U 0 )/n, therefore supporting the statement of universality. 14 The conclusion from the analysis of the universal relation with regard to the physical meaning of the ordinate variable Y/n is that, for a given E/n value, the dependence of the sputtering yield Y on the cluster size n is equivalent to the dependence of Y on the incident cluster energy E. This interpretation makes more physical sense because the cluster energy E is the primary factor inducing ejection rather than the cluster size n.…”
Section: Introductionmentioning
confidence: 58%
“…Due to high energy per cluster atom, individual cluster atoms penetrate into the bulk of the solid. 14 The penetration depth exceeds 2 nm. At the lowest E/n, the picture does not change much.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations